The Impact of Emotional attachment, Customer Experience, and Binge-Watching on SVOD Loyalty through Customer Satisfaction - Ni Luh Gde Sulastri Diva Astuti; Agus Fredy Maradona (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Technological progress has significantly accelerated the expansion of Subscription Video-on-Demand (SVOD) services, reshaping the way audiences access and enjoy digital entertainment. This study examines the effects of emotional attachment, customer experience, and binge-watching behavior on customer loyalty, with customer satisfaction serving as a mediating factor. A quantitative approach was employed using data from 250 respondents selected through a convenience sampling method. Data were collected via online questionnaires and analyzed using Structural Equation Modeling with the SmartPLS software. The results reveal that emotional attachment positively and significantly influences customer satisfaction, whereas customer experience and binge-watching show no significant impact. Additionally, emotional attachment, customer experience, binge-watching, and satisfaction do not have a significant direct effect on customer loyalty. Mediation analysis demonstrates that customer satisfaction mediates the relationship between emotional attachment and customer experience with loyalty, while binge-watching remains unaffected. These findings highlight the crucial mediating role of customer satisfaction in strengthening loyalty, emphasizing that emotional bonds and experiential factors foster long-term engagement, whereas binge-watching behavior tends to be temporary and does not contribute meaningfully to sustained loyalty among SVOD users.